Show your voice : a student-led university corporate engagement programme / Marni Jamil - Jamil, Marni (Academy of Language Studies, 2023)
Public Speaking 2 (HPD221) undergraduate students of Universiti Teknologi MARA (UiTMCPP) conducted a University Corporate Engagement programme called Show Your Voice under the supervision of their instructor, Ms Marni Jamil from the Academy of Language Studies, UiTMCPP. The student-led programme organised on 11 December 2022 from 8:00 AM until 12:00 PM at Laman Perdana, UiTMCPP, was generously sponsored by He & She Coffee, UiTMCPP and Digi Telecommunications. The programme participants were pre-commerce (PBA002/PBA003) students of the UiTM Pre-Higher Education Programme, UiTMCPP. In the first session, Ms Marni Jamil started the event by stressing the importance of inclusion and diversity, as well as building professional networking through her speech, Building Bridges and Longer Tables. Syed Amir Haikal Syed Hisyam Alwi, a UiTMCPP student who is a debate enthusiast, introduced the technological medium of idea-sharing via podcasting during his session, Know Your Voice: The Impact and Power of Podcasting.